2020
DOI: 10.1186/s12890-020-1107-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased respiratory morbidity in individuals with interstitial lung abnormalities

Abstract: Background: Interstitial lung abnormalities (ILA) are common in participants of lung cancer screening trials and broad population-based cohorts. They are associated with increased mortality, but less is known about disease specific morbidity and healthcare utilisation in individuals with ILA. Methods: We included all participants from the screening arm of the Danish Lung Cancer Screening Trial with available baseline CT scan data (n = 1990) in this cohort study. The baseline scan was scored for the presence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 39 publications
0
34
0
1
Order By: Relevance
“…It includes men and women born from 1907 to 1935; the average age of participants enrolled in this study amounted to seventy-six. Hoyer et al [ 35 ] reported that ILA subjects were subject to respiratory disease such as chronic obstructive pulmonary disease, lung cancer and pneumonia. However, the cause of death of participants was not identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It includes men and women born from 1907 to 1935; the average age of participants enrolled in this study amounted to seventy-six. Hoyer et al [ 35 ] reported that ILA subjects were subject to respiratory disease such as chronic obstructive pulmonary disease, lung cancer and pneumonia. However, the cause of death of participants was not identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, early diagnosis or more careful follow-up of ILAs may be required with the possibility of progression in mind. Increased comorbidities, such as lung cancer and other respiratory diseases, should also be considered during follow-up ( Table 5 ) [ 72 81 82 83 84 ].…”
Section: How Do We Understand the Whole Gamut Of The Ild Spectrum From Ila To Uip With A Special Focus On Traction Bronchiectasis/bronchimentioning
confidence: 99%
“…In addition to mortality, ILA have been associated with several disease processes. A lung cancer screening study has found an increased risk of ILD diagnosis among participants with ILA [ 19 ]. Patients with ILA have been found to have decreased odds of COPD and decreased COPD severity in a cohort study [ 5 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Patients with ILA have been found to have decreased odds of COPD and decreased COPD severity in a cohort study [ 5 ]. Still, a later case-control study among smokers failed to show a significant association with COPD and a lung cancer screening study has suggested increased risk of COPD diagnoses among participants with ILA [ 19 , 52 ]. Another study has associated ILA with Group B of the Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification of COPD [ 53 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation